2019
DOI: 10.1002/csr.1765
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development and human resource management: A science mapping approach

Abstract: This manuscript presents a systematic review of "sustainable human resource management" (HRM), highlighting its major themes and the evolution and tendencies observed in this field. It contributes to the development of this relatively new topic, offering a critical evaluation and identifying the highest impact research strands.The Web of Science database returned 111 documents spanning the period 1997-2018, and a conceptual science mapping analysis based on co-word bibliographic networks was developed, using S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 61 publications
2
32
0
2
Order By: Relevance
“…Based on the synergies observed between CSR and HRM and the contribution of SR‐HRM to the creation of value for individuals, organizations, and society, research on this topic has received special attention recently, as indicated by the growth of studies that relate CSR and HRM. However, the field still lacks conceptual maturity and practice due to the difficulty of stipulating which specific actions include SR‐HRM (Santana & Lopez‐Cabrales, 2019). Although efforts to define and concretize the specific actions covered by SR‐HRM can be found in the literature (e.g., Celma, Martínez‐Garcia, & Coenders, 2014; Diaz‐Carrion, López‐Fernández, & Romero‐Fernandez, 2018; Dupont, Ferauge, & Giuliano, 2013; Jamali et al, 2015), there is a need to promote discipline by establishing mechanisms that effectively allow its evaluation and comparison in a systematic way (Aust et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the synergies observed between CSR and HRM and the contribution of SR‐HRM to the creation of value for individuals, organizations, and society, research on this topic has received special attention recently, as indicated by the growth of studies that relate CSR and HRM. However, the field still lacks conceptual maturity and practice due to the difficulty of stipulating which specific actions include SR‐HRM (Santana & Lopez‐Cabrales, 2019). Although efforts to define and concretize the specific actions covered by SR‐HRM can be found in the literature (e.g., Celma, Martínez‐Garcia, & Coenders, 2014; Diaz‐Carrion, López‐Fernández, & Romero‐Fernandez, 2018; Dupont, Ferauge, & Giuliano, 2013; Jamali et al, 2015), there is a need to promote discipline by establishing mechanisms that effectively allow its evaluation and comparison in a systematic way (Aust et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to CSR, which is a related subtheme in the sustainable HRM research theme, Lu et al [22] empirically tested the connection between CSR specifically directed toward employees (CSRe) and career development sustainability. Although previous researchers have contributed to broaden the comprehension of the sustainable HRM concept, there is still a lack of research on how sustainable HRM is reflected through HR practices and how to measure this [77,78].…”
Section: Sub-period 2017-2019mentioning
confidence: 99%
“…The clean technology market today is represented by a wide range of products, services, and processes that provide productivity while reducing costs, including "environmental costs", by minimizing negative environmental impact [5]. So, why is there not enough experience in applying the requirements established by environmental legislation?…”
Section: Environmental Management Of Coal Mining Enterprises and Innomentioning
confidence: 99%